Efektivitas Edukasi Melalui Zoom Meeting Terhadap Pencegahan Dm Tipe 2 Pada Remaja Kelas Ix Di Smpn Xxx Palangka Raya - Marselinus, Heriteluna; Siti, Ajizah (Universitas Pahlawan Tuanku Tambusai, 2024)
Diabetes Mellitus (DM) is a non-communicable disease which is currently a health problem that is often complained about by people around the world, which is characterized by high levels of blood glucose in the body and is triggered by increasingly rapid population growth such as obesity, diet and lifestyle. unhealthy. Research Objectives: To determine the effectiveness of zoom meetings on the prevention of Type 2 Diabetes Mellitus in adolescents Research Methods: The pre-experimental method with the One Group Pretest Posttest design, with a total sample of 106 using the formula developed by Issac and Michael. Data collection used dietary questionnaires, physical activity questionnaires, diabetes mellitus questionnaires and weight and height observation sheets. Data analysis used the Kolmogorov Smirnov test. Research Results: Providing education to prevent type 2 diabetes mellitus through zoom meetings results in good knowledge as evidenced by the P value = 0.15 > ? 0.05.Conclusion: Education through zoom meetings on the prevention of type 2 diabetes mellitus has proven to be effective